The Routledge handbook of Byzantium and the Danube regions
1 online resource.
Keywords: "This volume aims to broaden and nuance knowledge about the history, art, culture, and heritage of Eastern Europe relative to Byzantium. From the 13th century to the decades after the fall of Constantinople in 1453, the regions of the Danube River stood at the intersection of different traditions and the river itself has served as a marker of connection and division, as well as a site of cultural contact and negotiation. The Routledge Handbook of Byzantium and the Danube Regions brings to light the interconnectedness of this broad geographical area too often either studied in parts or neglected altogether, emphasizing its shared history and heritage of the regions of modern Greece, Croatia, Serbia, Bulgaria, Romania, Hungary, Slovakia, Czechia. The aim is to challenge established perceptions of what constitutes ideological and historical facets of the past, as well as Byzantine and post-Byzantine cultural and artistic production in a region of the world that has yet to establish a firm footing on the map of art history. The twenty-four chapters offer a fresh and original approach to the history, literature, and art history of the Danube regions, thus being accessible to students thematically, chronologically, or by case-study; each part can be read independently or explored as part of a whole"--